2022
DOI: 10.1038/s41598-022-18819-z
|View full text |Cite
|
Sign up to set email alerts
|

Attention rhythmically samples multi-feature objects in working memory

Abstract: Attention allows us to selectively enhance processing of specific locations or features in our external environment while filtering out irrelevant information. It is currently hypothesized that this is achieved through boosting of relevant sensory signals which biases the competition between neural representations. Recent neurophysiological and behavioral studies revealed that attention is a fundamentally rhythmic process, tightly linked to neural oscillations in frontoparietal networks. Instead of continuousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…Conversely, detailed observation of our behavioral index (i.e., reaction time, RT) in tasks that require participants to recall sequential information would reveal temporal uctuation of neural activity realizing sequential working memory. Such behavioral uctuations have been reported in the eld of attention (Fiebelkorn et al, 2013;Helfrich et al, 2018;Landau & Fries, 2012;VanRullen, 2018) and working memory (Abdalaziz et al, 2023;Chota et al, 2022;Peters et al, 2021;Pomper & Ansorge, 2021). For instance, it was reported that the reaction time and detection rate for a stimulus in a location showed uctuation in the theta range, showing that even "sustained" attention is not stable but uctuates (Fiebelkorn et al, 2013;Helfrich et al, 2018).…”
Section: Introductionmentioning
confidence: 68%
“…Conversely, detailed observation of our behavioral index (i.e., reaction time, RT) in tasks that require participants to recall sequential information would reveal temporal uctuation of neural activity realizing sequential working memory. Such behavioral uctuations have been reported in the eld of attention (Fiebelkorn et al, 2013;Helfrich et al, 2018;Landau & Fries, 2012;VanRullen, 2018) and working memory (Abdalaziz et al, 2023;Chota et al, 2022;Peters et al, 2021;Pomper & Ansorge, 2021). For instance, it was reported that the reaction time and detection rate for a stimulus in a location showed uctuation in the theta range, showing that even "sustained" attention is not stable but uctuates (Fiebelkorn et al, 2013;Helfrich et al, 2018).…”
Section: Introductionmentioning
confidence: 68%
“…Accordingly, our microsaccade observations may signal serial refreshing by the oculomotor system that may serve as a mechanism supporting object maintenance. In future studies, it will be interesting to address whether and how these microsaccade findings relate to recent complementary findings of serial object-sampling in working memory (e.g., Chota et al, 2022; Peters et al, 2021; Pomper & Ansorge, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…Recently, similar observations have been made for object- 10 and feature-based 38 attention as well as abstract cue-guided visual perception 12 . It might also apply to related cognitive concepts, such as working-memory 39 or other sensory domains, such as audition 40 . Several lines of inquiry suggested that rhythmic brain activity in the frontoparietal attention network constitutes a viable mechanism that efficiently segregates attentional sampling from attentional shifting, i.e., separates sensory from motor functions 2 .…”
Section: Discussionmentioning
confidence: 99%